Avaliacao da qualidade de oleos vegetais sob estresse fotoxidativo e termoxidativo por espectroscopia de UV e RMN e H - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2008)
Photo and thermal oxidation effects on the stability of refined soybean, corn, canola and sunflower oils was evaluated by spectroscopy and titration methods in this work. Oils samples were submitted to oven test (63°C – 45 days) and photoxidation (room temperature – 4000 lux – 60 days). The antioxidants addition effects was evaluated on the oil protection during photoxidation. The results showed that the canola oil is more resistant to thermal and photoxidation while the sunflower oil shows less resistance. Good correlations between peroxide values and ultraviolet and 1H NMR data were found (correlation coefficients 0.962 to 0.996). The ultraviolet data indicated that the antioxidants effectiveness on the photoxidation oil protection was: propyl gallate (PG) > tert-butyl hydroquinone (TBHQ) > butilated hydroxytoluene (BHT) > butilated hydroxyanisole (BHA) > citric acid. The results showed that UV and NMR are efficient techniques to monitoring antioxidants effects, oxidative changes and vegetable oil quality control under thermal or photochemical stress.
Keywords: óleos vegetais; fotoxidação; termoxidação; antioxidantes; análise espectroscópica; vegetable oils; photoxidation; thermal oxidation; antioxidants; spectroscopy analysis; CNPQ::CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS